The Exploring of Marxism Regarding The Poverty Sustainability in Kampung Nelayan Seberang, Belawan, Indonesia - Bakhrul Khair Amal (Budapest International Research and Critics University, 2018)
The phenomenon of poverty and the trap of poverty is a social reality that cannot be understood without exploring the phenomenon itself. The focus of this dissertation study is to look at the phenomenon of poverty that occurred in Seberang Village with the subject of research is fishermen's family. The phenomenon of poverty that is reflected in the poverty trap that ensnares the society of opposite the fishing village deserves to be explored in depth. The falsity of class consciousness comes from the class position in the economic structure of society. In other words, the people of Seberang Fisherman's Village experienced a form of false consciousness, namely the form of